Vitamin D deficiency in girls from South Brazil: a cross-sectional study on prevalence and association with vitamin D receptor gene variants - Santos, Betânia R (BioMed Central, 2012)
BACKGROUND: Vitamin D deficiency has been associated with a multitude of disorders including diabetes, defective insulin secretion as well as rickets and poor bone health. Vitamin D is also a concern during childhood and adolescence and has been reported in girls from South Brazil. We determined the prevalence of vitamin D deficiency in girls from South Brazil and investigated whether the genotypic distribution of the BsmI, ApaI and TaqI polymorphisms of the VDR gene and their haplotypes were associated with vitamin D levels. METHODS: Cross-sectional study including 234 apparently healthy girls aged 7 to 18 years. Height and weight were measured for calculation of body mass index (BMI) percentiles for age. Plasma levels of 25-hydroxyvitamin D [25(OH)D] were assessed. Participants were genotyped for ApaI (rs7975232), TaqI (rs731236), and BsmI (rs1544410) SNPs. RESULTS: The median and interquartile range (25-75%) of BMI percentile was 62.0 (33.3 – 84.9). The frequency of overweight/obesity was 24.9%. Circulating levels of 25(OH)D (≥ 30 ng/mL) were adequate in 9.4%; insufficient in 54.3% (20–29 ng/mL); and deficient in 36.3% (< 20 ng/mL). Genotype frequencies were GG = 47.0%, GA = 41.5%, and AA = 11.5% for BsmI; GG = 16.7%, GT = 52.6%, and TT = 30.8% for ApaI; TT = 46.2%, TC = 44.9% and CC = 9.0% for TaqI. Genotypes with no gene variance (ancestral wild genotype) of BsmI (GG vs. GA + AA, two-tailed Student’s t-test p < 0.001), ApaI (GG vs. GT + TT, two-tailed Student’s t-test p = 0.031) and TaqI (TT vs. TC + CC, two-tailed Student’s t-test p = 0.005) SNPs and the GGT haplotype (two-tailed Student’s t-test p = 0.036) were significantly associated with lower 25(OH)D levels. CONCLUSIONS: 25-hydroxyvitamin D deficiency and insufficiency were highly prevalent in this sample. The BsmI, ApaI and TaqI wild variants of the VDR gene, as well as the GGT haplotype, were associated with lower vitamin D levels, suggesting that VDR gene polymorphisms could be linked to higher susceptibility to vitamin D deficiency in a sub-population of children and adolescents.